Oxidation of 2,5-diformfylfuran to 2,5-furandicarboxylic acid catalyzed by Candida antarctica Lipase B immobilized in a cyclodextrin-templated mesoporous silica. The critical role of pore characteristics on the catalytic performance - Decarpigny, Cédric; Bleta, Rudina; Ponchel, Anne; Monflier, Eric (Colloids and Surfaces B: Biointerfaces, 2021)
International audience HypothesisPorous silica has been extensively used as suitable carrier for the immobilization of various enzymes. Randomly Methylated β-Cyclodextrin (RaMeβCD) has surface active properties and very high solubility in water and could therefore be used as template in the fabrication of silica particles with tunable pore size.ExperimentsSilica particles were prepared by sol-gel process in alkaline medium with and without use of RaMeβCD. Lipase Bfrom Candida antarctica (CALB) was either incorporated within the pores of RaMeβCD-derived support or covalently attached on the surface of CD-free silica particles and its catalytic performance was assayed in the oxidation of 2,5-diformylfuran (DFF) to 2,5-furandicarboxylic acid (FDCA). Enzymatic reactors were characterized by N 2 -adsorption analysis, small angle XRD, TG/DSC experiments, ATR-FTIR spectroscopy, HR-TEM and LSCM, while reaction products were determined based on 1H NMR spectroscopy combined with HPLC.FindingsResults showed that the use of RaMeβCD as structure directing agent led to mesoporous silica composed of uniform 8 nm-sized particles with 11 nm-sized mesopores compatible with the dimensions of CALB (3.0 nm × 4.0 nm × 5.0 nm). Incorporation of CALB within the pores of RaMeβCD-derived silica caused almost a two-fold increase in specific activity after 7 h at 40 °C when compared to lipase immobilized on the surface of CD-free silica particles (33.2 μmol g −1 min −1 vs. 14.4 μmol g −1 min −1 ). Moreover, the RaMeβCD-derived biocatalyst demonstrated enhanced operational stability during the recycling experiments, retaining more than 90% of its initial activity after five 24 h-reaction cycles. These findings open up new avenues for future research on the use of cyclodextrins in the development of enzyme-based nanoreactors.